2005
DOI: 10.1002/ijc.21123
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lymph node metastasis in colorectal carcinoma by expressionof chemokine receptor CCR7

Abstract: Chemokine receptors are known to regulate homing of lymphocytes into secondary lymphoid organs and may also be involved in the lymphatic spread of solid tumors. Therefore, the assessment of chemokine receptor expression on colorectal carcinomas could potentially improve the prediction of lymph node spread. This is of great importance for the selection of patients for local therapy without the need for concomitant lymphatic dissection. Currently, only 5% of all patients can be selected for this desirable treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(119 citation statements)
references
References 41 publications
4
112
1
2
Order By: Relevance
“…In one report, immunohistochemistry revealed CXCR5 expression in a significant proportion of human colon carcinoma specimens (Gunther et al, 2005), whereas another group demonstrated cytoplasmatic expression in pancreatic cancer cells and cell lines (Meijer et al, 2006). We show here for the first time that the ligand for CXCR5, CXCL13, is the most significantly overexpressed chemokine in breast cancer, supporting the idea of a role of CXCL13/CXCR5 interactions in promoting initiation and/or progression of this tumour type and, possibly, other human cancers.…”
Section: Discussionsupporting
confidence: 68%
“…In one report, immunohistochemistry revealed CXCR5 expression in a significant proportion of human colon carcinoma specimens (Gunther et al, 2005), whereas another group demonstrated cytoplasmatic expression in pancreatic cancer cells and cell lines (Meijer et al, 2006). We show here for the first time that the ligand for CXCR5, CXCL13, is the most significantly overexpressed chemokine in breast cancer, supporting the idea of a role of CXCL13/CXCR5 interactions in promoting initiation and/or progression of this tumour type and, possibly, other human cancers.…”
Section: Discussionsupporting
confidence: 68%
“…breast, melanoma, gastric, non-small cell lung cancer, head and neck tumors, colorectal carcinoma), CCR7 is upregulated and mediates tumor cell dissemination to lymph nodes [101][102][103][104][105][106]. In a recent study, brain infiltration by T-cell leukemic blasts was mediated by CCR7 [15].…”
Section: Tumor Cell Invasion and Migration To Distant Organsmentioning
confidence: 99%
“…CCR7 plays a critical role in lymphocyte and dendritic cell trafficking into and within lymph nodes. Human cancer cells from malignant breast, gastric, oesophageal, NSCLC, squamous cell carcinoma of the head and neck and colorectal carcinomas express functional CCR7 [133,[165][166][167][168][169]. Cancer cells that over-express CCR7 can migrate towards its ligand CCL21, which is strongly expressed in lymph nodes [167,170].…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 99%
“…Recently, it has been reported that CCR7 activation on thyroid carcinoma cell by CCL21 favors tissue invasion and cell proliferation, and therefore may promote thyroid carcinoma growth and lymph node metastasis [172]. CCR7 is a potential marker to predict metastasis in breast and colorectal cancer and is correlated with disease progression [138,166]. In addition, patients with oral and oropharyngeal squamous cell carcinomas that express CCR7 have lower survival rates than those with CCR7-negative tumors [173].…”
Section: Chemokines and Their Receptors In Tumor Growth And Metastasismentioning
confidence: 99%